Strong and Efficient Cache Side-Channel Protection using Hardware Transactional Memory - Gruss, Daniel; Lettner, Julian; Schuster, Felix; Ohrimenko, Olya; Haller, Istvan; Costa, Manuel (USENIX Security Symposium 2017, 2017)
Abstract Cache-based side-channel attacks are a serious problem in multi-tenant environments, for example, modern cloud data centers. We address this problem with Cloak, a new technique that uses hardware transactional memory to prevent adversarial observation of cache misses on sensitive code and data. We show that Cloak provides strong protection against all known cache-based side-channel attacks with low performance overhead. We demonstrate the efficacy of our approach by retrofitting vulnerable code with Cloak and experimentally confirming immunity against state-of-the-art attacks. We also show that by applying Cloak to code running inside Intel SGX enclaves we can effectively block information leakage through cache side channels from enclaves, thus addressing one of the main weaknesses of SGX. The source code of basic experiments is available on GitHub.